Continuous versus intermittent cardiac output measurement in cardiac surgical patients undergoing hypothermic cardiopulmonary bypass - Böttiger, Bernd W.; Rauch, Helmut; Böhrer, Hubert; Motsch, Johann; Soder, Michael; Fleischer, Franz; Martin, Eike (Journal of cardiothoracic and vascular anesthesia, 1995)
Objective: - Continuous thermodilution cardiac output (CCO) measurement was clinically evaluated in patients who underwent coronary revascularization using hypothermic low-flow, low-pressure cardiopulmonary bypass (CPB). - Design: - Prospective study. - Setting: - University hospital setting. - Participants: - 30 cardiac surgical patients. - Interventions: - CCO was correlated to standard bolus thermodilution cardiac output (ICO) obtained at end-expiration. - Measurements and Main Results: - Measurements were taken at selected time points (n = 18) before anesthesia induction, before CPB, and 5 minutes to 12 hours after CPB. A total of 540 data pairs were thus obtained. ICO ranged from 1.9 to 9.9 L/min, CCO from 1.5 to 9.9 L/min. Correlation between ICO and CCO was highly significant (r = 0.872; p < 0.01), accompanied by an excellent accuracy (bias −0.0213 L) and precision (0.59 L) before CPB and more than 45 minutes after CPB. However, during the first 45 minutes after CPB, there was no correlation (r = 0.273) between ICO and CCO, and ICO tended to be relatively high, whereas CCO measurements showed relatively low values. During the first 45 minutes after hypothermic CPB, but not during the ensuing time period, central blood temperature decreased, which may be interpreted as a lack of thermal equilibration between central and peripheral compartments. It is hypothesized that thermal instability in combination with increased respiratory variations in pulmonary artery blood temperature caused inhomogenous rewarming of different body sites and might be the main reason for the lack of correlation between ICO and CCO. - Conclusions: - Despite an excellent correlation, accuracy, and precision between CCO and ICO before CPB and more than 45 minutes after hypothermic CPB, a lack of correlation in the early phase after CPB has been found. Further investigation is needed to elucidate the underlying cause of these findings and to clarify whether ICO or CCO or both fail to represent the real cardiac output up to 45 minutes after weaning from hypothermic CPB.
Elektronische Reproduktion der Druck-Ausgabe 25. August 2005
Gesehen am 07.05.2024